2016
DOI: 10.1364/oe.24.008097
|View full text |Cite
|
Sign up to set email alerts
|

Underwater wireless transmission of high-speed QAM-OFDM signals using a compact red-light laser

Abstract: We first study the transmission property of red light in water in terms of extinction coefficient and channel bandwidth via Monte Carlo simulation, with an interesting finding that red light outperforms blue-green light in highly turbid water. We further propose and experimentally demonstrate a broadband underwater wireless optical communication system based on a simple and cost-effective TO56 red-light laser diode. We demonstrate a 1.324-Gb/s transmission at a bit error rate (BER) of 2.02 × 10-3 ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(51 citation statements)
references
References 20 publications
0
51
0
Order By: Relevance
“…Subsequently, the authors in [33] demonstrated a UOWC system with the data rate of 4.8 Gbps using 16 quadrature amplitude modulationorthogonal frequency division multiplexing (QAM-OFDM). A UOWC system with the data rate of 4.88 Gbps was proposed in [34] by using 32 QAM-OFDM to get the transmission distance of 6 m. Recently, a 7.2 Gbps UOWC system has been proposed in [35] for 450 nm blue laser with the transmission distance of 6 m. Table I summarizes the comparison between three different kinds of underwater wireless communication systems.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the authors in [33] demonstrated a UOWC system with the data rate of 4.8 Gbps using 16 quadrature amplitude modulationorthogonal frequency division multiplexing (QAM-OFDM). A UOWC system with the data rate of 4.88 Gbps was proposed in [34] by using 32 QAM-OFDM to get the transmission distance of 6 m. Recently, a 7.2 Gbps UOWC system has been proposed in [35] for 450 nm blue laser with the transmission distance of 6 m. Table I summarizes the comparison between three different kinds of underwater wireless communication systems.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in the industry, the underwater transmission distance has been extended over 150 m with a data rate of 12.5 Mbps, as demonstrated by Sonardyne's BlueComm 200 system. Furthermore, the advancements of low-cost and energy-efficient light sources such as LEDs [11] and diode lasers [12] enable the construction of compact miniaturized optical transceivers for data, image, and video transmission [13].…”
Section: Introductionmentioning
confidence: 99%
“…A study on underwater transmission characteristics, attenuation coefficient, and channel bandwidth regarding blue, green, and red lights had been proposed, [7][8] from which an interesting finding was obtained-red light has a better transmission performance compared with blue and green lights in high turbidity water. [9][10][11][12][13][14] Therefore, an underwater wireless red-light laser transmission (UWRLLT) system is expected to provide a short-distance underwater highspeed link, similar to Wi-Fi-on-air in terms of function. In the situation of increasing popularity of oceanic exploration and oceanic leisure activities, the sense of distance experienced underwater or in the ocean is more obvious than that on the land.…”
Section: Introductionmentioning
confidence: 99%